2022
DOI: 10.3389/fphys.2022.1062397
|View full text |Cite
|
Sign up to set email alerts
|

Sex comparisons in physiological and cognitive performance during hypoxic challenge

Abstract: Within the tactical aviation community, human performance research lags in considering potential psychophysiological differences between male and female aviators due to little inclusion of females during the design and development of aircraft systems. A poor understanding of how male and female aviators differ with respect to human performance results in unknown potential sex differences on aeromedically relevant environmental stressors, perchance leading to suboptimal performance, safety, and health guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Previous work (Vento et al, 2022) supports our finding that biological sex has no effect on cognition with hypoxic gas; however, other normoxic work has shown sex differences in DB (Ferrante et al, 2020). Our data also showed no effect of ethnicity on DB and this has been supported by a survey investigating ethnicity and driving behaviors (Bergdahl, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Previous work (Vento et al, 2022) supports our finding that biological sex has no effect on cognition with hypoxic gas; however, other normoxic work has shown sex differences in DB (Ferrante et al, 2020). Our data also showed no effect of ethnicity on DB and this has been supported by a survey investigating ethnicity and driving behaviors (Bergdahl, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Examining the respiratory effects of hypoxia, Camacho-Cardenosa et al (2022) observed that males exhibited an elevation in minute ventilation and a more pronounced initial decline in capillary oxygen saturation in comparison to females during a 7-hour exposure to moderate hypoxia (FiO 2 : 15%) [27]. Furthermore, Vento et al (2022) identified markedly diminished capillary oxygenation levels and an increased occurrence of headache in females compared to males during acute hypoxia [28]. Despite the existence of studies that didn't observe sex differences [29,30], the inconsistence outcomes underpin the significance of investigating female responses to hypoxic stimuli.…”
Section: Introductionmentioning
confidence: 99%